Brief Alcohol Intervention among At-Risk Drinkers with Diabetes - Susan E. Ramsey; Patricia A. Engler; Magdalena Harrington; Robert J. Smith; Mark J. Fagan; Michael D. Stein; Peter Friedmann (SAGE Publishing, 2010)
Twenty-eight patients with diabetes who screened positive for at-risk drinking were assigned to brief alcohol intervention (BAI) (n = 14) or standard care (SC) (n = 14) treatment conditions. All participants completed a baseline interview and one-, three, and six-month follow-up interviews. Across the six-month follow-up period, there was a significantly greater reduction in quantity of alcohol consumed in the BAI group. At the six-month follow-up, the BAI group had a greater reduction in quantity of alcohol consumed, percentage of heavy drinking days, and frequency of drinking. Reductions in alcohol use were associated with improved adherence in certain components of diabetes self-care behavior. The results of this study suggest that brief alcohol interventions are efficacious in reducing alcohol use among at-risk drinkers with diabetes and that reductions in alcohol use may result in some improvements in adherence to diabetes self-care behavior.